NARATIVE REVIEW: POTENSI INULIN UMBI DAHLIA SEBAGAI ANTI DIABETES - Sunarti Sunarti; Chrismis Novalinda Ginting; Sahna Ferdinand Ginting (Universitas Prima Indonesia, 2022)
Inulin is a type of polysaccharide that is commonly found in nature derived from the dahlia tuber plant, and other plants such as chicory, Jerusalem artichoke, Yaco´n potato and asparagus. Inulin is widely used in industry and pharmaceuticals. In the industrial world, inulin is used as a source of natural sweetener, enhances the taste of food, ferments, and is a low-fiber food source. While in the pharmaceutical world, inulin can be used in several studies, one of which is as an anti-diabetic. This study aims to determine the potential of dahlia tuber inulin as an anti-diabetic. The type of research is a narrative review. Search data using three databases, namely Elsevier (SCOPUS), Pubmed and Google Scholar with a limitation of the last 10 years of articles with the keyword